Global small solutions of the cauchy problem for a semilinear system of equations of thermoelasticity - Botsenyuk, А. N. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For a semilinear system of equations of thermoelasticity, we establish a theorem on the existence and uniqueness of global solutions in a multidimensional space under the condition that the initial data are sufficiently small. We also obtain estimates for the decrease of solutions as time increases.